Pengaruh Penjualan Personal, Citra Merek, Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Produk PT Kingled Indonesia Medan - Angkasa, Dennis; Halim, Andrian; Faris, Salman; Betty, Betty; Tirawani, Suriati (Manajemen dan Bisnis, 2024)
PT. Kingled Indonesia is a company that holds the exclusive KINGLED brand, headquartered in Medan. It has been distributing its products throughout Indonesia since 2010. Kingled products have obtained ISO and SNI certifications. However, increasing competition has led to a decline in the company's sales, which is related to personal selling, brand image, and product quality. The population studied consists of all customers who made purchases from the company during 2022, totaling 779 stores. Because the population consists of 779 stores, the sample size was reduced using the Slovin sampling technique, with a confidence level of 90% and a margin of error of 10%, resulting in 87 samples. The research results show that personal selling has a positive and significant influence on purchasing decisions. Brand image also has a positive and significant influence on purchasing decisions. Product quality likewise has a positive and significant influence on purchasing decisions. Overall, personal selling, brand image, and product quality have a significant influence on purchasing decisions.